A comprehensive investigation of lipid-transfer proteins from Cicer arietinum disentangles their role in plant defense against Helicoverpa armigera-infestation - Saxena, Harshita; Negi, Harshita; Keshan, Radhika; Chitkara, Pragya; Kumar, Shailesh; Chakraborty, Amrita; Roy, Amit; Singh, Indrakant K.; Singh, Archana (Frontiers in Genetics, 2023)
Lipid Transfer Proteins (LTPs ) play a crucial role in synthesizing lipid barrier polymers and are involved in defense signaling during pest and pathogen attacks. Although LTPs are conserved with multifaceted roles in plants, these are not yet identified and characterized in Cicer arietinum. Therefore, a genome-wide analysis of LTPs was executed and their physiochemical properties, biochemical function, gene structure analysis, chromosomal localization, evolutionary analysis and promoter analysis were performed using in silico tools.Their tissue-specific expression analysis and gene expression analysis during pest attack were also conducted. A total of 48 LTPs were identified and named as CaLTPs. They were predicted to be small unstable proteins with "Glycolipid transfer protein" domain and "Alpha-Amylase Inhibitors, Lipid Transfer and Seed Storage" domain, that are translocated to the extracellular region. CaLTPs were predicted to possess 3-4 introns and were located on all the eight chromosomes of chickpea with half of the CaLTPs being localized on chromosomes 4, 5, 6 and found to be closely related to LTPs of Arabidopsis thaliana and Medicago trancatula. Gene duplication and synteny analysis revealed that most of the CaLTPs have evolved due to tandem or segmental gene duplication and were subjected to purifying selection during evolution. The promoters of CaLTPs had development-related, phytohormone-responsive, and abiotic and biotic stress-related cis-acting elements. A few CaLTP transcripts exhibited differential expression in diverse tissue types, while others showed no / very low expression. Out of 20 jasmonate-regulated CaLTPs, 14 exhibited differential expression patterns during Helicoverpa armigera -infestation, indicating their role in plant defense response. This study identified and characterized CaLTPs from an important legume, C. arietinum and indicated their involvement in plant defense against H. armigera-infestation, which can be further utilized to explore lipid signaling during plant-pest interaction and pest management.